THE INFLUENCE OF WORKING CAPITAL TURNOVER ON PROFITABILITY LEVELS IN TRADING COMPANIES IN THE REITEL SECTOR LISTED ON THE INDONESIAN STOCK EXCHANGE IN 2020-2022 - Andi Oca; Amrizal Salida; Muhammad Taufiq (Universitas Ichsan Sidenreng Rappang, 2024)
This research aims to determine the effect of working capital turnover on the level of profitability in trading companies in the retail sector listed on the Indonesian stock exchange. The research method used is a quantitative method with a descriptive approach to find the relationship between variables. The source of this research comes from financial reports through documentation techniques. The population in this study was 32 trading companies in the retail sector listed on the Indonesian stock exchange, while the sampling technique used was purposive sampling so that the sample obtained was 12 companies that met the criteria. The data analysis method used is multiple linear regression analysis. The results of this research show that partially Cash Turnover has no and insignificant influence on Profitability, Receivables Turnover has a positive and significant influence on Profitability. Then simultaneously Cash Turnover and Receivables Turnover have a positive and significant influence on Profitability.